Mitos Gajah : Relasi Gajah – Manusia di Balai Raja Bengkalis - Fajar Ramadhan; M Rawa El Amady; Yevita Nurti (Universitas Andalas, 2021)
This study discussed the myths of elephants in the community of Balai Raja Village, Pinggir District, Bengkalis Regency. The elephant myths are the patterns of human-elephant relationships. Before the 1980s, the relationship between elephants and humans was very harmonious. After 1980, the forestry and oil palm industries caused between elephants and humans, which has been occurring until now. This study is categorized into qualitative research with an ethnographic design. Researchers stayed in the field for 2 months to explore information in depth through observation and in-depth interviews. The data was analyzed qualitatively and then written in this report. This study has found out that the conflict between elephants and humans is determined by human attitudes and behavior. The myth of the elephant is a symbol of efforts to conserve natural resources and a tool for compliance with societal norms and values. Elephants have protective properties and are very empathetic to babies. This study proposes that elephant mitigation can use a mythical approach by combining elephants’ and human’s habitation. This study contributes to the science of Anthropology, especially about the conservation of animals and nature. This study proposes that elephants should not be called pests, but a chain of human mutualism, where the elephants and humans live in harmony as a unified ecosystem.